Social Enterprises and Eu Regulation - Rado, Bohinc (International Journal of Scientific Research and Management (IJSRM), 2019)
Social enterprises are very diverse across Europe. There is a wide range of different legislative approaches and different organisational and legal forms on the national level. In some countries, existing legal forms such as associations, foundations, cooperatives and share companies are used as social enterprises. In other countries, new legal forms are designed for social enterprises by adapting existing legal forms (companies, cooperatives), e.g. social cooperatives in Italy, cooperative collective interest companies in France, community interest companies in the UK.The reason for the variety of approaches how to implement the idea of social enterprise, is in the lack of uniform binding rules on the level of the EU. Here, we present our views on the legal framework needed to implement the concept of social entrepreneurship in the EU in a more efficient and effective manner.First, we present a range of definition of social entrepreneurship and enterprises, many of them not consistent and/or sufficiently elaborated. Further, some historical roots are presented on social and self-managed economy, and the concept of social enterprise is elaborated from the point of view of its eligibility. Comparative analysis aims to prove critical diversity of approaches across the EU that leads to stagnating in place and lagging behind.